Comparative Analysis of Neural Mobilization and Rhythmic Stabilization in Range of Motion and Hip Pain - Ponte, Samyla Maria Araújo; Souza, Leydnaya Maria; Costa, Bruno Cunha da; Gouveia, Guilherme Pertinni de Morais (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The hip is a structure of the human body in which occurs the junction of bone, articular, muscular and ligament structures. It is in the coxofemoral joint and has the function of supporting the whole-body weight, being one of the main joints responsible for ambulation. Objectives: To analyze the comparison of neural mobilization and rhythmic stabilization techniques in range of motion (ROM) and hip pain. Methods: The sample was composed by 20 patients, with mean age of 54±6 years, were divided into two groups of 10 patients: the patients who received the neural mobilization technique (G1) and the patients who received the rhythmic stabilization technique (G2). Results: The mean age of each group was 56±6 years (G1) and 52±6 years (G2). Among the evaluated, 12 (60%) were female, 14 (70%) were married, predominating the profession of housewife (35%). The great majority of the participants (95%) presented pain to the active movement, mainly to the movements of hip flexion and abduction. Regarding passive mobilization, 70% referred pains, predominating to the movements of hip external rotation and abduction. Conclusion: It was concluded that the neural mobilization and rhythmic stabilization techniques had satisfactory results in relation to ROM and pain in the hip region, but rhythmic stabilization had a greater gain of ROM and decrease of pain.